2014
DOI: 10.1111/pme.12553
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Neuropathic Pain after Cooled Radiofrequency Ablation of Sacral Lateral Branch Nerves

Abstract: The incidence of postprocedural neuropathic pain after cooled RFA for posterior sacroiliac joint complex denervation is low and in a similar range to that in the lumbar spine. We consider this procedure safe to be utilized by pain medicine practitioners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…As for the secondary effects, the cause of the neuropathic pain and buttock numbness that occurs after ablation is likely due to the middle cuneal nerve, which is formed by sacral lateral branches [28]. The buttock soreness we believe is due to the dissipated heat (60 °C) and inflammatory reaction which causes the muscles to be tense.…”
Section: Discussionmentioning
confidence: 88%
“…As for the secondary effects, the cause of the neuropathic pain and buttock numbness that occurs after ablation is likely due to the middle cuneal nerve, which is formed by sacral lateral branches [28]. The buttock soreness we believe is due to the dissipated heat (60 °C) and inflammatory reaction which causes the muscles to be tense.…”
Section: Discussionmentioning
confidence: 88%
“…No adverse events related to this procedure using thermal or cooled RFA have been reported in the published literature to date ( 8 - 12 ). However, post-procedural neuritis/deafferentation pain is a theoretical concern, as this is a known adverse event associated with RFA of the medial branch and sacral lateral branch nerves ( 23 - 25 ). Third degree skin burn has been reported with the use of C-RFA to denervate a thoracic medial branch nerve in a patient with a very thin body habitus ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies had also showed a higher presence of neuropathic pain after third occipital nerve RF (15%-55% and 19%) and lower incidence with cooled RF ablation of the sacral lateral branches. 37 39…”
Section: Discussionmentioning
confidence: 99%